DEFINITION ISSUES FORMS OF UNEMPLOYMENT AND THEIR SPECIFICS IN THE HISTORICAL AND LEGAL AND MODERN ECONOMIC CONDITIONS - Vladimirovich, Kudryavtsev Igor; Melievich, Mukhammedov Khaidarali; Omanturdievich, Kadirov Eshmukhamad (International Journal of Psychosocial Rehabilitation, 2020)
The article focuses on the analysis of the state and dynamics of employment, explores the problems of unemployment, as well as youth. The characteristics of the social and socio-psychological state of students and unemployed youth as well as the population, historical and international experience in the fight against unemployment are analyzed. The authors give definitions of unemployment as a socio-economic phenomenon that involves the absence of work among people who are economically active (economically active people are those who have or can have their own income. The economically active population does not include children, pensioners, women on maternity leave child and disabled.). More specifically, unemployment is a complex phenomenon that is characteristic of a market economy. The authors note an important problem of modern society - as unemployment, which is relevant today.